Dinamika Perikatan Dalam Peralihan Hak Atas Tanah Keluarga: Analisis Normatif dan Praktik Sosial - Dindin Syarief Nurwahyudin (Edulaw : Journal of Islamic Law and Yurisprudance, 2025)
This study discusses the dynamics of obligations in the transfer of family land rights by highlighting the tension between positive legal norms and social practices. Normatively, the transfer of land rights must fulfill the requirements of an agreement as stipulated in the Civil Code, be set forth in an authentic deed, and be registered in accordance with the provisions of the Basic Agrarian Law (UUPA) and Government Regulation No. 24 of 1997. However, in practice, transfers are often carried out in a simple manner through oral grants, private agreements, or customary family arrangements based on mutual trust. This phenomenon creates legal vulnerability and has the potential to trigger land disputes. This research employs a normative-sociolegal approach with qualitative analysis to examine land regulations as well as social practices. The research findings indicate the need for legal harmonization by positioning notaries/PPAT not merely as administrative officials, but also as legal educators who bridge formal law with the living law. The implications of this study highlight the crucial role of notaries/PPAT in preventing disputes, its contribution to the development of integrative agrarian law, and the opening of opportunities for further research on customary practices in various regions and more effective models of legal harmonization.